Genetic sequence characterization and naturally acquired immune response to Plasmodium vivax Rhoptry Neck Protein 2 (PvRON2) - Bittencourt, Najara C (BMC, 2018)
BACKGROUND: The genetic diversity of malaria antigens often results in allele variant-specific immunity, imposing a great challenge to vaccine development. Rhoptry Neck Protein 2 (PvRON2) is a blood-stage antigen that plays a key role during the erythrocyte invasion of Plasmodium vivax. This study investigates the genetic diversity of PvRON2 and the naturally acquired immune response to P. vivax isolates. RESULTS: Here, the genetic diversity of PvRON21828-2080 and the naturally acquired humoral immune response against PvRON21828-2080 in infected and non-infected individuals from a vivax malaria endemic area in Brazil was reported. The diversity analysis of PvRON21828-2080 revealed that the protein is conserved in isolates in Brazil and worldwide. A total of 18 (19%) patients had IgG antibodies to PvRON21828-2080. Additionally, the analysis of the antibody response in individuals who were not acutely infected with malaria, but had been infected with malaria in the past indicated that 32 patients (33%) exhibited an IgG immune response against PvRON2. CONCLUSIONS: PvRON2 was conserved among the studied isolates. The presence of naturally acquired antibodies to this protein in the absence of the disease suggests that PvRON2 induces a long-term antibody response. These results indicate that PvRON2 is a potential malaria vaccine candidate.